Sonochemical synthesis, photocatalysis and photonic properties of 3% Ce-doped ZnO nanoneedles - Yayapao O. (2014)
ZnO nanostructured particles doped with 0-3% Ce were successfully synthesized by an ultrasonic solution method. Phase and morphology characterized by XRD, FTIR, SEM, TEM, HRTEM, SAED and EDX revealed the presence of hexagonal wurtzite ZnO nanoneedles with E2H vibration at 426 cm-1, composing of the corresponding elements and growing in the [0 0 1] direction. The 3% Ce-doped ZnO nanoneedles showed the 3.00 eV direct energy gap and 392.6 nm emission by UV-visible absorption and photoluminescence (PL) spectroscopy, including the most effective photocatalytic activity in the solution containing methylene blue. © 2012 Elsevier Ltd and Techna Group S.r.l.